Navigating 'riskscapes': The experiences of international health care workers responding to the Ebola outbreak in West Africa. (May 2017) - Gee, Stephanie; Skovdal, Morten
Abstract: This paper draws on interview data to examine how international health care workers navigated risk during the unprecedented Ebola outbreak in West Africa. It identifies the importance of place in risk perception, including how different spatial localities give rise to different feelings of threat or safety, some from the construction of physical boundaries, and others mediated through aspects of social relations, such as trust, communication and team dynamics. Referring to these spatial localities as 'riskscapes', the paper calls for greater recognition of the role of place in understanding risk perception, and how people navigate risk. Highlights: We explore how international health care workers perceived and navigated risk during the 2013-2016 Ebola outbreak. Perceptions of risk in health care workers were shaped by both physical and relational factors. 'Riskscapes' are the structures, people, relationships and policies that shape, and are shaped by, perceptions of risk. Limited resources and occupational safety protections for staff resulted in a reduction in the quality of care that was able to be provided to patients. Constructing places of safety was necessary to allow mental reprieve from fears of infection. Interpersonal and institutional trust arose as key factors in attenuating perceptions of risk in health care workers.